(untitled) - Sherer, Mary Alice Statkiewicz (St. Louis, MO, 2002)
Thoroughly updated and revised, this time-tested features full color illustrations and a vibrant, easy-to-use design. Information is presented in a style that builds from basic to more complex concepts. It covers essential information on the biological effects of ionizing radiation and radiation protection, helping readers ensure the safe medical use of ionizing radiation. The book also discusses radiation physics, cell structure, effects of radiation on humans at the cellular and systemic levels, regulatory and advisory limits for human exposure to radiation, and the implementation of patient and personnel radiation protection practices. The 4th edition features new illustrations, more review questions, and extensive new and updated material throughout.
Keywords: Radiography,,Medical; Safety measures